Planning of New Products Technological Mastering and its Influence on Economic Indicators of Companies - Novikova, Nina V.; Barmuta, Karine A.; Kaderova, Venera A.; Il'yaschenko, Dmitry P.; Abdulov, Rafael E.; Aleksakhin, Alexander V. (International Journal of Economics and Financial Issues, 2016)
Improving the quality of services or improve product quality at the modern stage of economic development is one of the most important factors in the growth of production efficiency. The quality of products or services is essential to “stay afloat” and an important factor towards success in the market in conditions of tough competition. In the conditions of market relations in various companies and organizations the relevance of quality management is characterized by its focus on the formation of such level of quality products and services, which can absolutely meet all the needs of consumers. Maintaining the high quality of services and products is the main component that determines their competitiveness. Without consistency of quality, which meets the requirements of consumers in the market, it becomes impossible to integrate the national economy into the global economic management and to take in it high. A stable increase in the quality of products by enterprises is regarded currently as the main condition of its competitiveness on internal and foreign markets. The competitiveness of products or services largely determines the status of the country and is a fundamental factor of increasing its national wealth. Keywords: competitiveness, planning, technological development, investment costs, product quality, economic performance, R&D JEL Classifications: O14, O21, O32, O33